Peran pendidikan dalam pembentukan moral generasi muda - Syam Rigel Atria Dipdha, Kalya Khairanaya, Nilna Izza Billah (Maliki Interdisciplinary Journal, 2026)
This article discusses the essential role of education in shaping the moral character of young generations amid increasingly complex moral challenges in the modern era. Various phenomena such as bullying, misuse of social media, and deviant behavior reveal a moral crisis that demands serious attention from the educational system. Through a literature review, this article analyzes the current moral condition of youth, the role of educational institutions as a space for character formation, and the teacher’s role as a moral role model. The discussion also highlights the challenges of moral development in the digital age and proposes long-term strategies for strengthening moral values through collaboration between schools, families, and social environments. The findings emphasize that education plays a strategic role in forming morally upright and responsible individuals capable of adapting to modern societal changes. Systematic, consistent, and adaptive character education is crucial in shaping morally grounded and integrity-driven young generations.